30th anniversary of RAACS: Saving and continuing the best traditions of the national architectural and construction school - Lyakhovich, Leonid (project baikal, 2023)
Project Baikal journal publishes the reports of RAACS academicians at the Jubilee General Meeting of members of the Russian Academy of Architecture and Construction Sciences, which was held from 11 to 13 October 2022 in the Central House of the Architect, Moscow.L. Lyakhovich, academician and head of the Siberian Regional Branch of the RAACS, outlined the history of the Academy in Russia since 1764 up to the present time and highlighted important aspects of the RAACS activities. He emphasized that the activities of its members have greatly determined the strategy for the development of living environment.
Keywords: RAACS; Academy; history of construction and architecture; building industry; construction; architecture